Comparison of Beam Structure Calculations Using SNI 03-2847-2013 with British Standard 8110-01-1997 - Fiana, Rafa Okta; Usmanul Hayadi Umar; Savitri, Amanatullah (Journal of Civil Engineering and Planning (JCEP), 2024)
There are many regulations that can be used as work standards in planning building structures. Structural Concrete Requirements for Buildings SNI 03-2847-2013 is the standard used in Indonesia, but other standards, such as British Standard 8110-01-1997, are also used. The aim of this research is to determine the difference in beam structure calculations using the SNI 03-2847-2013 method and British Standard 8110-1997. In this research, the analysis method includes preparation, calculation and drawing conclusions, as well as recommendations. The calculation stage includes a comparison of SNI 03-2847-2013 with British Standard 8110-01-1997. The calculation results show different reinforcement dimensions for SNI and British Standard.